Peranan Lembaga Konsultasi dan Bantuan Hukum (LKBH) dalam Menangani Kasus Sengketa Perdata Akibat Cidera Janji : Penelitian - Dara Puspitasari; Ika Ayudyanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Business growth in Indonesia has resulted in an increase in civil disputes, particularly those resulting from breaches of business agreements. Many small and medium enterprises (MSMEs) experience difficulties accessing legal services due to financial constraints and limited legal knowledge. In this context, Legal Consultation and Aid Institutions (LKBH) play a strategic role in providing legal assistance and ensuring access to justice. This study uses a juridical-sociological method with a qualitative descriptive approach. The results indicate that LKBH's role in handling business breaches includes litigation and non-litigation assistance, legal consultation, and mediation. The main obstacles faced by LKBH include limited human resources and operational funds. This study recommends strengthening LKBH's capacity through institutional support and synergy with the government and business actors.